La quinina, el símbolo de la XXII Olimpiada Iberoamericana de Química-2017 - Nakamatsu, Javier; Gonzales Gil, Patricia (Pontificia Universidad Católica del Perú, 2019)
Quinine, present in the bark of the cinchona tree, native to the South American Andes, is one of the natural medicines that has saved more lives in the history of humanity. Its economic importance, as a treatment for malaria, generated a search for its synthetic route. This promoted the development of organic synthesis and marked the beginning of industrial organic chemistry. Quinine, a compound so connected not only with the history of Peru but also with that of organic synthesis, was highlighted in the XXII Ibero-American Chemistry Olympiad-2017.

La quinina, presente en la corteza de la quina (Cinchona) que es originaria de los Andes sudamericanos, es uno de los medicamentos naturales que ha salvado más vidas en toda la historia de la humanidad.  Su importancia económica como tratamiento contra la malaria generó la búsqueda de una ruta para su síntesis, lo cual promovió, a su vez, el desarrollo de la síntesis orgánica y marcó el inicio de la química orgánica industrial.  La quinina, tan vinculada no solo a la historia del Perú sino a la de la síntesis orgánica, fue resaltada en la XXII Olimpiada Iberoamericana de Química-2017
Quinine, the symbol of the XXII Ibero-American Chemistry Olympiad-2017
Keywords: Quinina; Síntesis orgánica; Productos naturales; https://purl.org/pe-repo/ocde/ford#1.04.00